JOBLIST DOKUMENTASI BERBASIS WEBSITE DENGAN iLEARNING WIKIS - Dewi Immaniar; Untung Rahardja; Jetty Susanti (Universitas Raharja, 2013)
Teaching and learning process in education is a core activity. This process is the interaction that occurs between faculty and students as well as influenced by existing activities. The use of integrated information systems to process the job sector in the organization has become an absolute necessity. However, such systems generally do not provide a container to encapsulate all the information to help evaluate student performance. In addition the number of scattered data in a database system resulted in a massive copy process at any time require the data. Thus, the existence of this reality by using Wikis iLearning data can be displayed in a container that allows a work history of development and there is one report display tasks can be neatly arranged to facilitate the search. Monitoring evaluation of student performance will be more focused to achieve a successful student project. This paper attempts to describe the problems faced in an information system, especially in the documentation of student performance evaluation, explanation iLearning Wikis, architecture, program listings, as well as diagrams. In the prototype implementation is shown a graph of the data development and documentation of student work. Wikis iLearning is a website joblist documentation that provides reports and data storage facilities provide user profile information. Implementation of Wikis can be used to provide solutions to the problems in teaching and learning in particular database storage